The practical use of the Social Network (Face Book) by teachers in the Basic Education Stage in the Educational Process and obstacles that limit them (Field study according to some taxonomic variables) - قاسم رهام علي; حسامو سهى علي; كحيلة مرح عبد الحميد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The study aimed to identify the practical use of the Social Network (Face Book) by a sample of male/ female teachers of the first stage in the basic education in the Educational Process and the extent of their use, and employment in the educational process, in addition to identify the obstacles that limit the use of them.In order to answer the questions of the study, and to explain the significant differences in the practical use teachers in the Basic Education Stage the face book in the Educational Process according to the variables of (gender, scientific qualification, duration of use the face book, teaching experience). To achieve this purpose, the researcher prepared a questionnaire consisting of (38), and the descriptive approach is used. The sample consisted of (68) male/ female teachers of the first stage of basic education in the public schools of LattakiaThe study showed that the reality of using teachers in the basic education stage the social network (Facebook) in the educational process was a medium, and there are no statistically significant differences between the average teacher’s answers to use the Face Book in the Educational Process according to variables: gender, scientific qualification, duration of use and teaching experience. The study recommended hiring face book in the field of education, and the creation of official pages of teachers of all discipline and stages to exchange ideas and educational views and teaching experience. In addition, to encouraging teachers to positive use in the educational process.